2023
DOI: 10.1021/acs.analchem.3c00142
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Fluorescent Probe for Simultaneous Detection of ONOO, Viscosity, and Polarity and Its Application in Ferroptosis and Cancer Models

Abstract: Intracellular peroxynitrite anions (ONOO–) and microenvironments (such as viscosity and polarity) play an important role in maintaining redox homeostasis, regulating diffusion, transportation, and signal transduction in living cells. The abnormality of these factors is often closely related to various physiological/pathological processes. However, owing to the lack of suitable probes, the simultaneous visualization of ONOO–, viscosity, and polarity in ferroptosis and cancer models has not been achieved. To mee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…Fluorescent probes have become a popular tool for real-time imaging and exploration of various physiological processes due to their advantages of high sensitivity, excellent resolution, non-invasiveness, and fast response compared to other technologies. 11 To date, a large number of fluorescent probes have been developed for the monitoring of various physiological processes in LDs. 12–14 For instance, in 2022, the team of Peiyao Xie 15 designed a fluorescent probe TPA-SO2 , which can simultaneously detect SO 2 and LD polarity during ferroptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescent probes have become a popular tool for real-time imaging and exploration of various physiological processes due to their advantages of high sensitivity, excellent resolution, non-invasiveness, and fast response compared to other technologies. 11 To date, a large number of fluorescent probes have been developed for the monitoring of various physiological processes in LDs. 12–14 For instance, in 2022, the team of Peiyao Xie 15 designed a fluorescent probe TPA-SO2 , which can simultaneously detect SO 2 and LD polarity during ferroptosis.…”
Section: Introductionmentioning
confidence: 99%
“…These functional and structural changes forebode the mitochondrial abnormality. Viscosity, as one of the crucial microenvironmental parameters for characterizing the mitochondrial state, is believed that monitoring its changes will help us to understand the function during ferroptosis. By monitoring the changes in fluorescence intensity, Dong and co-workers discovered that the increased viscosity occurred during the ferroptosis . However, since intensity-dependent probes are easily disturbed by various factors (external microenvironments, instrument parameters, photobleaching), they are not appropriate for accurate analysis. Therefore, there is an urgent need to develop a precise tool for the quantitative analysis of mitochondrial viscosity changes during ferroptosis.…”
Section: Introductionmentioning
confidence: 99%
“…By monitoring the changes in fluorescence intensity, Dong and co-workers discovered that the increased viscosity occurred during the ferroptosis. 18 However, since intensity-dependent probes are easily disturbed by various factors (external microenvironments, instrument parameters, photobleaching), they are not appropriate for accurate analysis. 19−21 Therefore, there is an urgent need to develop a precise tool for the quantitative analysis of mitochondrial viscosity changes during ferroptosis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…•− ) reacts with nitric oxide (NO). 40 It has previously been reported that ONOO − can promote oxidative damage and induce lipid peroxidation, and it can further trigger ferroptosis. 41 The ROS changes will therefore be appropriately reflected by reliable and precise ONOO − detection, which may significantly aid in the elucidation of its biological consequences during ferroptosis and further enable thorough investigation and manipulation of ferroptosis.…”
mentioning
confidence: 99%
“…Peroxynitrite (ONOO – ) is a type of ROS that is usually generated when superoxide (O 2 •– ) reacts with nitric oxide (NO) . It has previously been reported that ONOO – can promote oxidative damage and induce lipid peroxidation, and it can further trigger ferroptosis .…”
mentioning
confidence: 99%